2003
DOI: 10.1002/pmic.200300394
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers of hepatitis B virus infected liver inflammation: A proteomic study

Abstract: Hepatitis B virus (HBV), a serious infectious and widespread human pathogen, represents a major health problem worldwide. Chronic HBV infection has a very high risk of evolving into hepatocellular carcinoma. Although considerable progress was made during the recent past, the pathogenesis of HBV infection is still elusive and a definite diagnosis of HBV infected liver information still relies on biopsy histological test. In this report, we used proteomics technology to globally examine HBV infected serum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 40 publications
3
115
1
4
Order By: Relevance
“…Of the 66 cases of nonmalignant disease, 63 were recognized as not cancer. This result yielded a sensitivity of 100%, specificity of 95% (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99), and PPV of 94% (101). Although the limitations of this study design and its analysis have been discussed in some detail in the literature (103)(104)(105)(106), the potential implications of such proteomic spectrum analysis for the identification of novel tumor markers is huge.…”
Section: Trials In the Generalmentioning
confidence: 99%
“…Of the 66 cases of nonmalignant disease, 63 were recognized as not cancer. This result yielded a sensitivity of 100%, specificity of 95% (87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99), and PPV of 94% (101). Although the limitations of this study design and its analysis have been discussed in some detail in the literature (103)(104)(105)(106), the potential implications of such proteomic spectrum analysis for the identification of novel tumor markers is huge.…”
Section: Trials In the Generalmentioning
confidence: 99%
“…Triplicate electrophoreses were performed to ensure reproducibility. All gels were visualized by silver staining [He et al, 2003]. Image acquisition and analysis were performed with an Image Scanner (Amersham) and Image Master 2D Elite software (Amersham).…”
Section: Treatment Of N2a Neuroblastoma Cells With Cadmium and Analysmentioning
confidence: 99%
“…These protein spots were cut off in small pieces and subjected to in-gel trypsin digestion overnight. Peptide mass spectra were recorded and previously described parameters for spectral acquisition were used [He et al, 2003]. Protein identification with 25 ppm or lower mass error and MOWSE scores over 300 were obtained in most analyses during database matching using MS-Fit (http://prospector.ucsf.…”
Section: Treatment Of N2a Neuroblastoma Cells With Cadmium and Analysmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, some spots from a different area were identified as a protein, such as haptoglobin (spot3, 4, 5, 6 and 7). The change of the spot's pI and Mr on serum 2-DE maps might be explained by post-translation modifications or different translation splicing, such as phosphorylation and glycosylation (23).…”
Section: Discussionmentioning
confidence: 99%